Solar-Powered Insect Trap Lamp to Support Food Security for Vegetable Farmers at BBPP Lembang, Bandung - Nana Sutarna; Isdawimah; Ahmad Tossin Alamsyah; Yogi Widiawati; Murie Dwiyaniti; Mera Kartika Delimayanti; Aminudin Debateraja; Oktivasari, Prihatin (Society : Jurnal Pengabdian Masyarakat, 2026)
The excessive use of chemical pesticides in vegetable cultivation has negative impacts on both the environment and human health. This community service activity aimed to introduce and implement a solar-powered insect trap (solar light trap) as an environmentally friendly alternative for pest control. The program was carried out in collaboration with the Sugih Mukti Farmers Group under the guidance of BBPP Lembang, Bandung. The applied methods included training, joint assembly of the device with students, as well as demonstration and handover of the tool to farmers. The results showed that this technology received positive responses from the farmers and has the potential to reduce pesticide use. Furthermore, the tool’s effectiveness was monitored to support a scientific publication. This activity represents a concrete step in applying appropriate technology to improve the quality of environmentally friendly agriculture.